Hotel Stock Price Performance During the Covid-19 Pandemic in Indonesia - Regina Sandra Kusuma; Arthik Davianti (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the Indonesian hotel stock price performance during the pandemic of Covid-19 by testing the effect of Covid-19 pandemic on stock return and abnormal stock return. The data were collected from secondary data at www.finance.yahoo.com, Indonesian hotel companies stock period from 26 February 2020 to 2 March 2020 during the pandemic of Covid-19. Further, the data were analyzed by using Event Study Methodology to examine the effect of Covid-19 pandemic on Indonesian hotel stock return and abnormal return. The result of this study finds that there is stock reaction after the announcement of Covid-19 pandemic in Indonesia during 15 days after the announcement. Also in this research, can be found a relationship between the stock condition with the pandemic. This research can be used as a reference for investors for their investments by looking at the relationship between the Indonesian hotel companies stock and pandemic of Covid-19.